AN EXPRESSIVE CRITICISM AGAINST POWER RELATION COVERED BY RELIGION IN "CHILDREN OF THE ALLEY" - IWAN KURNIAWAN (2008)
The novel Children of the Alley by Naguib Mahfouz pictured about the problems and suffering of Egypt's people, made by power relation in authority and government having used religion cover to protect their legitimation, and this novel also gives an academic critic and conveys dream's character to solve people,s problems and stop the crime. The researcher used qualitative methois used to collect and analyze the data in doing the research. The researcher also uses the theory of expressivis used to explain the qualitative data, opening up the history of characters and relating it with author's thoughts and perspective background.